2010
DOI: 10.1002/chem.201000298
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Epoxidation by H2O2/MeCN Catalysed by Cyclopentadienyloxidotungsten(VI) and Molybdenum(VI) Complexes: Experiments and Computations

Abstract: Compounds [Cp*(2)M(2)O(5)] (M = Mo, 1; W, 2) are efficient pre-catalysts for cyclooctene (COE) epoxidation by aqueous H(2)O(2) in acetonitrile/toluene. The reaction is quantitative, selective and takes place approximately 50 times faster for the W system (k(obs) = 4.32(9)x10(-4) s(-1) at 55 degrees C and 3x10(-3) M concentration for the dinuclear complex, vs. 1.06(7)x10(-5) s(-1) for the Mo system). The rate law is first order in catalyst and COE substrate (k = 0.138(7) M(-1) s(-1) for the W system at 55 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 53 publications
7
83
1
Order By: Relevance
“…Higher activity of W species is sometimes claimed and associated with a lower activation barrier for the rate-limiting step involving the transfer of the O a atom to the olefin [48,50]. Specifically, natural bond orbital and natural population analysis studies suggested that the tungsten center may withdraw electron density from the r bonding [OAO] orbital more strongly than a molybdenum center, lowering the r ⁄ [OAO] orbital energy and thus facilitating nucleophilic attack of the olefin.…”
Section: Epoxidation Of Cis-cyclooctenementioning
confidence: 97%
See 1 more Smart Citation
“…Higher activity of W species is sometimes claimed and associated with a lower activation barrier for the rate-limiting step involving the transfer of the O a atom to the olefin [48,50]. Specifically, natural bond orbital and natural population analysis studies suggested that the tungsten center may withdraw electron density from the r bonding [OAO] orbital more strongly than a molybdenum center, lowering the r ⁄ [OAO] orbital energy and thus facilitating nucleophilic attack of the olefin.…”
Section: Epoxidation Of Cis-cyclooctenementioning
confidence: 97%
“…Computational studies have suggested that the reaction mech- [48][49][50]. Higher activity of W species is sometimes claimed and associated with a lower activation barrier for the rate-limiting step involving the transfer of the O a atom to the olefin [48,50].…”
Section: Epoxidation Of Cis-cyclooctenementioning
confidence: 97%
“…[39] This effect has been observed for these and other reactions. [36,38,40] handle. However, it was found that other Mo(II) complexes, namely [Mo(η 3 -C 3 H 5 )(CO) 2 X(L 2 )] (4) (Chart 1), could be oxidized in situ by TBHP to produce active Mo(VI) species.…”
Section: Methodsmentioning
confidence: 98%
“…Kinetic experiments gave much insight on the mechanism, [34] which was extensively studied by DFT methods, by some of us, [12,13,35] and other groups. [36,37,38] A detailed report on olefin epoxidation promoted by the complex 3 (or analogues, with Cl instead of CH 3 , for instance) can be found in a previous publication. [13] Complex 3 by itself is not a catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, epoxides are produced by the epoxidation of alkenes with stoichiometric amount of peracid as oxidant, which is hazardous and environmentally undesirable. In order to overcome this disadvantage, some studies have been dedicated to the epoxidation of alkenes with organic oxidants (m-CPBA, CHP or TBHP) or inorganic oxidants (H 2 O 2 , NaClO or O 2 ) [4][5][6][7][8][9][10]. Among these oxygen donors, molecular oxygen is the most desired oxidant with respect to the economic consideration.…”
Section: Introductionmentioning
confidence: 99%